The effect of anthelmintic treatment on growth and sexual development of javanese thin-tailed ram lambs reader under village conditions - I. K. Sutama; Beriajaya . (Hemera Zoa, 1991)
A n experiment was conducted to determine the effect of internal parasite control, using a broad spectrum anthelmintic (Tetramisole) or a long-acting narrow spectrum anthelmintic (Disophenol) on growth and sexual development of Javanese thin - tailed ram lambs reared underville conditions. Treatment with a broad spectrum anthelmintic for controlling Hemonchus spp., alone did not result in a similar improvement in weight gain (39.8 g/day). The untreated group grew at a rate of 42,2 g/day. Neither anthelmintic treatment nor birth type (single or twins) significantly affect sexual development of lambs under village conditions, though single born ram lambs grew at significantly (P.01) faster rate than those or twins (57.5 vs 31.8 g/day).